Mafhūm al-ṣalawāt ‘inda majmū‘at Joged Shalawat Mataram: Dirāsah fī al-ḥadīth al-ḥayy - Suryadilaga, Muhammad Alfatih (Studia Islamika, 2014)
This study examines the spiritual dance tradition of Joged Shalawat Mataram (JSM), a spiritual dance originating from the Mataram Sultanate of Yogyakarta. The focus of this research study is to determine the meaning of ṣalawah in the JSM community. The results of this study are as follows. Firstly, JSM is a socio-cultural phenomenon emanating out of religious traditions, classified as a spiritual dance or art of spiritual movements. Secondly, JSM is a phenomenon of ‘living’ hadith. In this sense, the JSM tradition is based on hadith that reflect some basic principles of the Prophet—those that command the reading of ṣalawah to the Prophet and those that command the following of the Prophet’s character. Thirdly, JSM is a phenomenon of symbols of religious culture. Fourthly, as a socio-religious movement JSM wants to convey the values of character education through Islamic art.DOI: 10.15408/sdi.v21i3.1220